2017
DOI: 10.1016/j.neuropharm.2016.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Orbitofrontal participation in sign- and goal-tracking conditioned responses: Effects of nicotine

Abstract: Pavlovian conditioned stimuli can acquire incentive motivational properties, and this phenomenon can be measured in animals using Pavlovian conditioned approach behavior. Drugs of abuse can influence the expression of this behavior, and nicotine in particular exhibits incentive amplifying effects. Both conditioned approach behavior and drug abuse rely on overlapping corticolimbic circuitry. We hypothesize that the orbitofrontal cortex (OFC) regulates conditioned approach, and that one site of nicotine action i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 75 publications
1
23
2
Order By: Relevance
“…There was a trend for enhancement of sign‐tracking, but only in rats that were experienced with EtOH. These data indicate that nicotine affects goal‐tracking conditioned approach to an EtOH cue more strongly than sign‐tracking, which is in contrast with studies of nicotine's effects on cues that predict nondrug reinforcers (but see Stringfield et al., ). We had originally hypothesized that nicotine would enhance sign‐tracking to an EtOH cue because nicotine generally increases conditioned approach elicited by a combined auditory and visual Pavlovian EtOH cue (Maddux and Chaudhri, ) and specifically increases sign‐tracking to other nondrug reinforcers (Palmatier et al., ; Versaggi et al., ).…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…There was a trend for enhancement of sign‐tracking, but only in rats that were experienced with EtOH. These data indicate that nicotine affects goal‐tracking conditioned approach to an EtOH cue more strongly than sign‐tracking, which is in contrast with studies of nicotine's effects on cues that predict nondrug reinforcers (but see Stringfield et al., ). We had originally hypothesized that nicotine would enhance sign‐tracking to an EtOH cue because nicotine generally increases conditioned approach elicited by a combined auditory and visual Pavlovian EtOH cue (Maddux and Chaudhri, ) and specifically increases sign‐tracking to other nondrug reinforcers (Palmatier et al., ; Versaggi et al., ).…”
Section: Discussioncontrasting
confidence: 85%
“…Ultimately, we did not find that EtOH cues uniformly promoted sign‐tracking over extended conditioning as has been shown previously (Srey et al., ), although we did see a trend toward a decrease in goal‐tracking that began around week 6. Interestingly, one other study looking at the effects of nicotine on PavCA elicited by a nondrug cue has also reported substantial increases in goal‐tracking responses (Stringfield et al., ). Thus, nicotine may affect conditioned responding to both drug and nondrug cues by increasing approach toward an individual's prepotent cue (either the cue or the goal), as has been shown with opioid drugs (DiFeliceantonio and Berridge, ), and therefore, this form of conditioning may be highly susceptible to individual variation.…”
Section: Discussionmentioning
confidence: 99%
“…In Pavlovian-based tasks, when given concurrently with the initiation of a conditioned approach session where ethanol is the unconditioned stimulus, nicotine enhances approach behavior, though not when administered repeatedly in days leading up to the beginning of behavior sessions (Maddux and Chaudhri, 2017 ). Moreover, we and others have observed that nicotine is sufficient to elevate conditioned responding to cues predicting sucrose or water reward (Olausson et al, 2004a , b ; Stringfield et al, 2017 ), suggesting non-specific elevation of conditioned responding. It is unknown if exposure to nicotine prior to ethanol self-administration sessions can lead to such an escalation of ethanol seeking, as would be indicated by the Gateway Hypothesis for nicotine (Kandel and Kandel, 2014 ).…”
Section: Introductionmentioning
confidence: 54%
“…However, this may be due to nicotine’s well-known ability to enhance the reinforcing properties of conditioned cues (Donny et al, 2003 ; Olausson et al, 2004a , b ; Chaudhri et al, 2006 ; Palmatier et al, 2007 , 2013 ; Caggiula et al, 2009 ; Guy and Fletcher, 2014a , b ; Yager and Robinson, 2015 ). Indeed, several studies reported that nicotine administered prior to each behavioral session elevated conditioned responding to cues predicting either sucrose (Palmatier et al, 2013 ; Stringfield et al, 2017 ) or ethanol (Maddux and Chaudhri, 2017 ), supporting the contention that nicotine enhances approach behavior. Moreover, presentation of a nicotine-associated context, and not necessarily in the presence of nicotine, can increase ethanol self-administration (Zipori et al, 2017 ), suggesting the possibility that nicotine-enhancement of contextual cues is what actually drives enhanced ethanol seeking.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation